Design, performance, and calibration of CMS forward calorimeter wedges - (:unkn) unknown (SPRINGER, 2008)
We report on the test beam results and calibration methods using high energy electrons, pions and muons with the CMS forward calorimeter (HF). The HF calorimeter covers a large pseudorapidity region (3 <= vertical bar eta vertical bar <= 5), and is essential for a large number of physics channels with missing transverse energy. It is also expected to play a prominent role in the measurement of forward tagging jets in weak boson fusion channels in Higgs production. The HF calorimeter is based on steel absorber with embedded fused-silica-core optical fibers where Cherenkov radiation forms the basis of signal generation. Thus, the detector is essentially sensitive only to the electromagnetic shower core and is highly non-compensating (e/h approximate to 5). This feature is also manifest in narrow and relatively short showers compared to similar calorimeters based on ionization. The choice of fused-silica optical fibers as active material is dictated by its exceptional radiation hardness. The electromagnetic energy resolution is dominated by photoelectron statistics and can be expressed in the customary form as a/root E circle plus b. The stochastic term a is 198% and the constant term b is 9%. The hadronic energy resolution is largely determined by the fluctuations in the neutral pion production in showers, and when it is expressed as in the electromagnetic case, a = 280% and b = 11%.
Keywords: QUARTZ-FIBER CALORIMETER; TEST BEAM; PROTOTYPE; SIMULATION; RADIATION